Dampak Kebijakan Bantuan Sosial terhadap Masyarakat di Desa Wotan Kecamatan Sukolilo Kabupaten Pati Tahun 2023 - Aisyah Sausan Fadhila; Tijan (Universitas Negeri Semarang, 2025)
This study examines the impact of providing social assistance BLT DD, BPNT, PKH, and 10 kg Rice Food Assistance in Wotan Village. The purpose of this study is to find out the implementation of social assistance in Wotan Village, the impact of social assistance policies on the community and the factors that affect it. This research uses a qualitative approach. Data sources include data sources and secondary, data collection techniques using interviews, observations, and documentation. The data validity technique used is the triangulation technique. Data analysis through data collection, data reduction, data presentation, and conclusion making. The implementation of social assistance policies in Wotan Village has a positive impact in the form of increasing people's purchasing power, quality of life, and access to public services. Meanwhile, the negative impacts caused are dependence, misuse of aid funds and data, and become a financial burden on the state. The community feels that assistance is a right that must be given and getting additional income by becoming a recipient of assistance is a legitimate way for them. The political actors involved experienced miscommunication, making the distribution of aid run inappropriately. In addition, research shows that there are various factors that affect ranging from economic, political, cultural, and educational factors.